1997
DOI: 10.1007/s004420050282
|View full text |Cite
|
Sign up to set email alerts
|

Predation and bark beetle dynamics

Abstract: Bark beetle populations may undergo dramatic fluctuations and are often important pests in coniferous forests. Their dynamics are thought to be primarily driven by factors affecting the resistance of the host tree to attack, i.e., bottom-up forces, while natural enemies are usually assigned a minor role in these systems. I present behavioral experiments that suggest that the clerid beetle Thanasimus dubius may be an important source of mortality for the bark beetle Dendroctonus frontalis during attack of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 48 publications
4
144
0
6
Order By: Relevance
“…(Coleoptera: Scolytidae) and its predator Thanasimus dubius (F.) (Coleoptera: Cleridae): adult T. dubius are in high abundance 302 N. Warzée et al on the bark surface of attacked trees, can inflict more than 60% mortality to SPB adults and their densities exhibit yearly oscillations phase-shifted with respect to those of SPB [24,28]. In the USA, a predator/prey model based upon the T. dubius/D.…”
Section: Introductionmentioning
confidence: 99%
“…(Coleoptera: Scolytidae) and its predator Thanasimus dubius (F.) (Coleoptera: Cleridae): adult T. dubius are in high abundance 302 N. Warzée et al on the bark surface of attacked trees, can inflict more than 60% mortality to SPB adults and their densities exhibit yearly oscillations phase-shifted with respect to those of SPB [24,28]. In the USA, a predator/prey model based upon the T. dubius/D.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have not identified which natural enemies are most responsible for the delayed response, the common predator Thanasimus dubius (F.) (Coleoptera: Cleridae) is a promising candidate. This predator appears to be a significant source of D. front&s mortality (Thatcher & Pickard, 1966;Tumbow et&., 1978;Reeve, 1997;Reeve & Turchin, 2000), and high densities of T. dubius are often associated with declining and low level D. frontalis populations (Billings, 1988;Reeve, 1997;Turchin etal., 1999), as would be expected if they are agents of delayed density dependence. Adult T. dubius arrive almost immediately after mass attack is initiated, attracted by the pheromones of D. frontalis (Vim & Williamson, 1970;Dixon & Payne, 1979a).…”
Section: Introductionmentioning
confidence: 99%
“…Hábitat y hábitos. La gran mayoría de los miembros que componen el género Enoclerus son depredadores de larvas y adultos de otros insectos tanto en estadios inmaduros como en la etapa adulta; generalmente son asociados a plantas herbáceas y arbustivas en zonas tropicales y subtropicales sobre las cuales se encuentran depredando una amplia gama de insectos (Mawdsley 2001), aunque un número limitado de ellos se encuentra fuertemente asociado a especies de coníferas en bosques de clima templado, alimentándose de una extensa variedad de escarabajos descortezadores, siendo importantes reguladores poblacionales de estos mismos (Bunt et al 1980;Dixon & Payne 1980;Lawson & Morgan 1992;Billings et al 1996;Reeve 1997;Opitz 2002;Reeve et al 2003;Bentz 2006;Domínguez-Sán-chez et al 2008;Hansen et al 2009). Estatus y clasificación.…”
Section: Resultsunclassified
“…Todos los especímenes involucrados fueron identificados por el primer autor. Las muestras fueron colectadas mediante el uso de trampas multiembudo tipo Lindgren (Lindgren 1983), utilizando la feromona frontalina (1,5-dimetil-6-8-dioxabiciclo[3.2.1] octano), cebando cada trampa con una proporción fija de fórmula sintética la cual consistió en una dosis de 400 µl de capacidad de baja densidad de microcentrífuga de polietileno conteniendo 300 µl de frontalina racémica (Chemtica Internacional, San José, Costa Rica) (Moreno et al 2008), con dosis universal para todos los sitios de muestreo por trampa; la frontalina es un acetato bicíclico producido de forma natural por varias especies del género Dendroctonus (Lawson & Morgan 1992;Billings et al 1996;Reeve 1997;Paine et al 1999;Barkawi et al 2003, ), se utilizaron otros atrayentes como señuelos los cuales fueron colocados junto con la dosis previamente señalada de la feromona frontalina específicamente de la siguiente forma: los ejemplares obtenidos en el estado de Chiapas fueron colectados a partir de octubre de 2003 hasta agosto del 2004, utilizando los siguientes tratamientos: 1) testigo (ausencia de feromona y otros atrayentes), 2) aguarrás y 3) frontalina. Las colectas en el estado de Michoacán fueron llevadas a cabo desde junio de 2005 hasta septiembre de 2006 con el atrayente químico frontalina, no se utilizó ningún tipo de combinación con otros atrayentes.…”
Section: Materials Y Métodosunclassified